Connexin gap junction channels and chronic rhinosinusitis. Issue 6 (25th February 2016) - Kim, Raymond; Chang, George; Hu, Rebecca; Phillips, Anthony; Douglas, Richard
Abstract : Background: Gap junction channels are formed by connexin (Cx) proteins. These channels facilitate communication between adjacent cells, and some have been implicated in acute and chronic inflammation. We investigated whether altered connexin expression could be associated with the inflammatory changes of the sinonasal mucosa that characterize chronic rhinosinusitis (CRS). Our aims were first to screen normal sinus mucosa to determine the expression profile of the connexin family of genes, and second to compare the level of expression of 3 key connexins (Cx26, Cx30, and Cx43) in CRS and normal sinus mucosa. These 3 connexins have been implicated in lower airway epithelial cell repair, as well as chronic and acute cutaneous wounds. Methods: Sinus mucosa biopsies were taken from 11 patients with CRS undergoing sinus surgery and from 7 controls with normal sinuses undergoing transnasal pituitary surgery. Gene expression study of the connexin family was performed using polymerase chain reaction (PCR). Subsequent targeted quantitative analyses were done using quantitative real‐time PCR (qPCR) and fluorescent immunohistochemistry (IHC). Results: A total of 16 different connexin genes were expressed in the normal mucosa including Cx26, Cx30, and Cx43. The qPCR demonstrated increased abundance of Cx26 ( p = 0.005), Cx30 ( p = 0.07), and Cx43 ( p = 0.04) in CRS compared to control mucosa. IHC confirmed significantly higher levels of Cx43 in CRS ( p < 0.001). Conclusion: The majority of the connexin family is expressed in normal sinus mucosa. Expression of 3 selected connexins was found elevated in CRS mucosa. Connexin gap junction modulation may offer a novel therapeutic target for CRS.